Luz e Cena : Processos de comunicação co-evolutivos - Camargo, Roberto Abdelnur (2006)
Processes of communication may be treated as a scene and, in every scene, lighting has a preponderant importance. In spite of that, the role of lighting in all processes of communication is neglected by the specific bibliography in the area. The goal of this thesis is to investigate the relation between lighting and scene, based upon the corpomidia theory (KATZ & GREINER 1999, 2000, 2001, 2003, 2005), with a hypothesis that contradicts the hegemonic tendency of considering lighting as something that is separated from the process of communication in theatre. Lighting and scene should be seen as co-evolutive phenomena if we understand that all kinds of body in the world negotiate their permanence with the environment, what implies in constant exchange of information between them. This exchange involves adjustments in both parts and makes them always codependents. The first chapter brings a reflection about the main works published concerning the theme, describing and discussing the usual methods employed in stage lighting. The second chapter exploits the question from the viewpoint of the corpomidia theory, proposing that lighting and scene change and evolve themselves permanently, in real time, one directly influenced by the other. The last chapter discusses two performances: an example of stage lighting that contradicts the corpomidia theory a nd another one that is in accordance to it